Returns predictability of Malaysian bank stocks : Evidence and implications - Lim, Kian Ping; Tan, Hui Boon; Law, Siong Hook (Universiti Utara Malaysia, 2007)
The main objective of this study is to address the question of whether stock prices follow random walk all the time. Using the samples of four Malaysian bank stocks- Hong Leong Bank, Malayan Banking, Public Bank and Southern Bank, coupled with the Hinich and Patterson (1995) windowed-testing procedure, the results show that the series under study follow a random walk for long periods of time, only to be interspersed with brief periods of strong linear and non-linear dependency structures. Unlike previous studies, this paper provides a different perspective on the subject of random walk. In addition to that, several important implications drawn from the findings are also provided in the paper.